Cinderella II [videorecording (DVD)] : dreams come true ; Cinderella III, a twist in time - Kafka, John director; Nissen, Frank; Hale, Jennifer, 1972-; MacNeille, Tress; Paulsen, Rob, 1956-; Blakeslee, Susanne (Disney DVD., 2012)
Cinderella II: As a newly crowned princess, Cinderella learns that life at the Palace and her royal responsibilities are more challenging that she had imagined.